Comparative performance study of HC-12, nRF24L01, and XBee for vehicular communication - Sumendra Yogarayan; Siti Fatimah Abdul Razak; Mohd. Fikri Azli Abdullah; Afizan Azman; Vethanayagi Arultas; Suneetha Sri Raman (Institute of Advanced Engineering and Science, 2023)
In recent times, the volume of traffic congestion has been rapidly growing on roads. These days the necessity of having safe transportation and journey is essential. Thus, vehicle communication could be a possible solution to enhance safe transit. Vehicular communications provide a wide range of applications with different characteristics, namely vehicle and vehicle (V2V) communications. Every year, traffic accidents kill many people worldwide, and many people have been injured. V2V communication enables vehicles to communicate with each other to provide safety and convenience to drivers. Therefore, this paper explores a direction to develop a conceptual approach to V2V communication with HC-12, nRF24L01, and XBee. The study aims to analyze and evaluate the communication range that may contribute to the future road transportation system.